Enhancing Segway scooter optimization for adaptive stability with proportional derivative control system - Artanto, Dian; Pranowo, Ignatius Deradjad; Sutyasadi, Petrus (Institute of Advanced Engineering and Science, 2025)
This study presents a locally manufactured Segway scooter utilizing a proportional derivative (PD) control system for adaptive stability under load variations. The system employs a lookup table correlating PD parameters with user weight categories (50–60 kg, 60–70 kg, 70–80 kg). Constructed from lightweight steel and powered by a 24 V lithium-ion battery, the prototype supports up to 85 kg while maintaining energy efficiency. Experimental results confirm the PD controller’s effectiveness in achieving stability with minimal oscillation across all tested loads. It sustains a steady- state error below 0.5° (50–60 kg) and under 1° (70–80 kg), with oscillations under 7° and recovery from 35° disturbances. Compared to complex methods like genetic algorithms or fuzzy logic, the PD system offers greater simplicity and cost-efficiency. It matches fuzzy-PID stability while reducing computational overhead by 20–40% and power consumption to 10–20 W/s, outperforming conventional PID in dynamic load adaptability. The integration of PD control with locally sourced materials underscores the solution’s sustainability and practicality, providing a scalable, energy- efficient paradigm for personal transportation with robust performance across varying conditions.